2002
DOI: 10.1002/1521-4141(200202)32:2<541::aid-immu541>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine induction by purified lipoteichoic acids from various bacterial species - Role of LBP, sCD14, CD14 and failure to induce IL-12 and subsequent IFN-γ release

Abstract: We have recently shown that highly purified lipoteichoic acid (LTA) represents a major immunostimulatory principle of Staphylococcus aureus. In order to test whether this translates to other bacterial species, we extracted and purified LTA from 12 laboratory‐grown species. All LTA induced the release of TNF‐α, IL‐1β, IL‐6 and IL‐10 in human whole blood. Soluble CD14 (sCD14) inhibited monokine induction by LTA but failed to confer LTA responsiveness for IL‐6 and IL‐8 release of human umbilical vein endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 41 publications
5
87
0
1
Order By: Relevance
“…This is in accordance with the reports by Schrö-der et al (32) showing a CD14 dependence of LTA-induced activation of human monocytes by inhibition with anti-CD14 antibodies and Lotz et al (52), who showed a role for CD14 in the activation of neutrophil granulocytes by LTA. In contrast, Hermann et al (36) described that cytokine production in human whole blood was inhibited by the addition of sCD14, and sCD14 was not able to confer a response to LTA on endothelial cells. This contradiction might reflect different roles of soluble and membrane-bound CD14 in cell activation by LTA.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is in accordance with the reports by Schrö-der et al (32) showing a CD14 dependence of LTA-induced activation of human monocytes by inhibition with anti-CD14 antibodies and Lotz et al (52), who showed a role for CD14 in the activation of neutrophil granulocytes by LTA. In contrast, Hermann et al (36) described that cytokine production in human whole blood was inhibited by the addition of sCD14, and sCD14 was not able to confer a response to LTA on endothelial cells. This contradiction might reflect different roles of soluble and membrane-bound CD14 in cell activation by LTA.…”
Section: Discussionmentioning
confidence: 94%
“…Interaction of LTA with serum proteins has been reported previously, but the data published on the requirement of soluble LBP are conflicting. Thus, it has been reported that recombinant human LBP enhances the response of human monocytes to LTA preparations (32), whereas in another publication no influence of recombinant murine LBP on the cell activation of human monocytes could be observed (35,36). The discrepancy of these observations might be due to species-specific effects or differences in the test systems employed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It may be related to whether the bacteria is gram-negative or -positive. 61 Alternatively, anthrax lethal toxin (lethal factor ϩ PA) inhibits dendritic cell maturation 62 and kills macrophages, 63 which would selectively compromise immune responsiveness and favor bacterial survival.…”
Section: Discussionmentioning
confidence: 99%
“…For peptidoglycan, these immune stimulatory effects are controversially discussed and might be due to LTA contaminations [29,30]. Therefore, we used only LTA, which induces a cytokine profile different from LPS [31,32] and signals via TLR2 [33].…”
Section: Introductionmentioning
confidence: 99%